2016
DOI: 10.1097/aog.0000000000001693
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Blood Loss in Women Treated for Intrahepatic Cholestasis of Pregnancy

Abstract: OBJECTIVE To evaluate postpartum blood loss in women with treated intrahepatic cholestasis of pregnancy. METHODS In a retrospective case-control study, 15,083 deliveries including 348 women with intrahepatic cholestasis of pregnancy (2.3%) were analyzed from 2004 to 2014. To adjust for differences in baseline characteristics, a propensity analysis was performed and women in the control group were matched to the women in the intrahepatic cholestasis of pregnancy group in a 5:1 ratio. , meconium staining (14.5% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 17 publications
1
29
0
1
Order By: Relevance
“…[16] Additionally, various reports have suggested that severe ICP but not mild ICP is associated with poorer perinatal outcomes when compared to control populations. For example, Furrer et al found that MSAF was observed more often in women with severe ICP than in women without ICP, [17] while Raz et al determined that severe ICP increased the risk of preeclampsia, as compared with controls. [18] Notably, Glantz et al reported that the risk of fetal complications (spontaneous preterm delivery, asphyxia, and MSAF) increased by 1% to 2% per additional μmol/L of SBA above 40 μmol/L.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16] Additionally, various reports have suggested that severe ICP but not mild ICP is associated with poorer perinatal outcomes when compared to control populations. For example, Furrer et al found that MSAF was observed more often in women with severe ICP than in women without ICP, [17] while Raz et al determined that severe ICP increased the risk of preeclampsia, as compared with controls. [18] Notably, Glantz et al reported that the risk of fetal complications (spontaneous preterm delivery, asphyxia, and MSAF) increased by 1% to 2% per additional μmol/L of SBA above 40 μmol/L.…”
Section: Discussionmentioning
confidence: 99%
“…[14–16] Furthermore, several studies have provided evidence that, compared with control populations, severe ICP is associated with adverse fetal and maternal outcomes (including spontaneous preterm delivery, fetal asphyxia, MSAF, and preeclampsia) whereas mild ICP is not. [3,17,18] Furthermore, for maternal SBA levels >40 μmol/L, significant relationships were identified between SBA level and preterm delivery, spontaneous preterm delivery, stillbirth, and MSAF. [19] However, it remains unknown whether the risk of adverse perinatal outcomes remains elevated in women who are initially diagnosed with severe ICP but whose SBA levels are subsequently maintained <40 μmol/L by treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Cui et al 37 Furrer et al 24 Kowalska-Kańka et al 38 Zhang et al 26 Ataalla et al 36 15 countries, from five continents, were included in the aggregate data meta-analysis, whereas IPD data were available from 14 countries, from five continents.…”
Section: Subtotalmentioning
confidence: 99%
“…Incidence of OC in present study is 5%. Padmaja et 11 al and Ge et al found highest incidence of 8.2% and 6.5% respectively whereas Hafeez et al, 12 Sohail et al, 13 Furrer et al 14 and Rook et al 15 found lower incidence of OC that is 3.1%, 2.8%, 2.3% and 1.9% respectively. The cause of so much variation from present study is may be due to geographical variation, ethnicity, environmental factor, different food habits or sample size calculation.…”
Section: Discussionmentioning
confidence: 95%